Kesediaan murid Tahun 1 mengikuti pengajaran kemahiran proses sains dalam bahasa Inggeris - Sulaiman, Tajularipin; Konting, Mohd Majid (Faculty of Education, University of Malaya, 2014)
The Ministry of Education has implemented English as the medium of instruction for Science subject in primary schools in 2003. The students were the most affected by this change. It worries that students would begin to lose their interest and lack of confidence in learning Science. While, teachers and students should be confident with their opinion in order to teach the subject. In addition, the implementation of this teaching also raises problems to the rural students. The students in the rural areas who are not as prone to use English in their daily lives will have problems and are less willing which in turn can cause lose interest and fall behind in their studies. therefore, this study focused on the following aspects: a) to compare the readiness of the Year 1 students in the urban and rural areas to master the process skills and proficiency of Science in English terms, and b) to examine the readiness of Year 1 students to learn the process skill of Science in English.